1981
DOI: 10.1038/bjc.1981.258
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic effects of haematoporphyrin derivative on synchronized and asynchronous cells of different origin

Abstract: Summary.-Phototherapy in the presence of haematoporphyrin derivative has been shown to have a preferential effect on malignant tumours when compared to normal tissue. This communication presents a comparison of the sensitivity to photochemotherapy in vitro of different cell lines.Asynchronous populations of cells were exposed to light in the presence of haematoporphyrin derivative, and found to be inactivated with a comparable efficiency. The lines were of human, Chinese-hamster or mouse origin and had differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

1983
1983
2001
2001

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 22 publications
1
9
1
Order By: Relevance
“…The uptake of HpD and the resulting photosensitivity are generally found to be similar in transformed and normal cells in vitro (Chang & Dougherty 1978;Christensen et al, 1981;. The present study indicates that a slightly higher amount of HpD is strongly retained in the transformed cells of type III (Table I).…”
Section: Discussionsupporting
confidence: 68%
“…The uptake of HpD and the resulting photosensitivity are generally found to be similar in transformed and normal cells in vitro (Chang & Dougherty 1978;Christensen et al, 1981;. The present study indicates that a slightly higher amount of HpD is strongly retained in the transformed cells of type III (Table I).…”
Section: Discussionsupporting
confidence: 68%
“…This is supported by the similarity in drug uptake between exponentially growing and plateauphase cells (Table I). In contrast to the results of Christensen et al (1981), Gomer & Smith (1980) showed no cell cycle response, further supporting the notion of cell line dependent, growth phase related differences.…”
Section: Discussioncontrasting
confidence: 54%
“…There is an increase in the proportion of G1-like cells with increasing WiDr culture age from 68 (day 6 cultures) to 78% (day 12) (15% increase (West et al, 1988)). It has been shown that, for some cell lines, G1 cells are the most resistant of cells in the cell cycle to photodynamic treatment (Christensen et al, 1981). It is possible that WiDr cells show a variable cell cycle response with G1 resistance and that the increase in proportion of G1 cells in plateau-phase cultures accounts for resistance to PDT.…”
Section: Discussionmentioning
confidence: 99%
“…The response of a cell to PDT may vary with its position in the cell cycle (7). This could lead to colonies with different sensitivity to PDT provided that a significant degree of synchrony existed within the colonies.…”
Section: Methodsmentioning
confidence: 99%